Retracing a Historical Waterway and its Impact on the Community Life of Tangail City, Bangladesh - Faruk, Omar; Rashid, Masud Ur (Global Journal of Cultural Studies, 2023)
Modern urbanism is consuming significant features of the land comprehensively to accommodate the massive population to accelerate economic growth. The navigation system of the Bengal Delta is one of the most affluent and beneficiary features in Bangladesh. Tangail is a city near the capital of Bangladesh (Dhaka) situated on the bank of the Louhojong River. In the colonial period, there was an essential canal through the town, which inspired and shaped the core layout of the city. Several historically important pieces of architecture were also built on both sides of the canal. This study traces the lost navigation and only historically important riparian landscape, architecture, and community spaces, which was spatially connected by the water source. The study emphasizes social and urban interaction with landscape and architecture. It takes the help of mapping and qualitative research to simulate the community activities of the colonial city. The research illustrates the impact of a water source on a community-responsive city. An analysis of how the city consumed the most important historical evidence can be visualized through illustrations based on the demonstrations of a local history-conserving organization and the evidences collected from local inhabitants.